Challenges for Social Enterprises in Latvia - Kalkis, Henrijs; Vilka, Lolita; Līcīte-Ķurbe, Lāsma; Trapenciere, Ilze; Urbāne, Marta (Social Enterprise in Central and Eastern Europe, 2021)
The term “social enterprise” (SE) is not very common in Latvia, be it in academic circles or at the political level. The Global Entrepreneurship Monitor report, published in 2009, defined social entrepreneurship as “individuals or organisations engaged in entrepreneurial activities with a social goal”. Academic research in economics plays the leading role in the analysis and study of social enterprise in Latvia. In the last years, the interest of junior researchers in social enterprises has grown rapidly. Analysis of the concept of social entrepreneurship on the basis of various information sources demonstrates that the introduction of this concept in Latvia has been gradual. The concept of social partnership was used in municipalities as a step towards more intense public participation and the use of direct-democracy tools in the work of the administration. The common feature of these various terms is their association with a social-benefit activity.